Occupational use of agrochemicals results in inhibited cholinesterase activity and altered reproductive hormone levels in male farmers from Buea, Cameroon. Issue 2 (15th February 2021) - Manfo, Faustin Pascal Tsagué; Suh, Christian Fusi; Nantia, Edouard Akono; Moundipa, Paul Fewou; Cho-Ngwa, Fidelis
Abstract: The efficiency of agro pesticides and fertilizers in eliminating pests and scaling up crop yield has motivated farmers to increase their use. Unfortunately, health hazards caused on farmers by these agrochemicals are of growing concern, though not well elucidated. In order to evaluate the effects of occupational exposure to agrochemicals on some key parameters of male farmers' health in Buea Subdivision, Cameroon, a total of 101 men, including 62 farmers using the agrochemicals and a reference population of 39 men not involved in occupational utilization of the agrochemicals, were interviewed on use of protective equipment, exposure symptoms and reproductive health status. Thereafter, serum cholinesterase [acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE)] activities, total antioxidant capacity and reproductive hormones [follicle-stimulating hormone (FSH), luteinizing hormone and testosterone] were assessed. Results revealed that farmers mainly used insecticides followed by fungicides, herbicides and fertilizers, but with inadequate protective measures. The use of agrochemicals resulted in several exposure symptoms including weakness, itches, burning sensation, headache, sneezing, coughing and vomiting, as well as decrease in serum AChE activity when compared to the reference population. The agrochemicals impacted negatively on the farmers' reproductive health as evidenced by increased FSH levels. Taken altogether, these results suggested that exposure to agrochemicals adversely affects farmers' health. Therefore, there is a need to further sensitize the farmers on the use of protective equipment to mitigate the exposure and resulting health hazards.